2015
DOI: 10.6000/1929-4247.2015.04.04.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bilirubin Encephalopathy in Calabar, South-South, Nigeria (A 5-Year Review)

Abstract: Background: Bilirubin encephalopathy is the clinical syndrome associated with bilirubin toxicity to the central nervous system resulting in chronic and permanent sequelae. It has been estimated that approximately 60% of term babies and 80% of preterm babies develop jaundice within the first week of life.Objective: To determine the prevalence, morbidity and mortality of bilirubin encephalopathy at our centre.Methodology: A retrospective descriptive review of the case files of all babies diagnosed with bilirubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
7
2
1
Order By: Relevance
“…The present study observed a prevalence rate of 5.3% of conjunctivitis among hospitalized neonates. This is higher than 1.1% and 4.1% reported by Ochigbo et al from Nigeria and Goel et al from India respectively [3,18] , but lower than the 7.2%, 8.0% and 8.2% observed by other researchers from India, Togo and the United Kingdom respectively. [10,14,19] However, it has been pointed out that the incidence of neonatal conjunctivitis tends to vary widely from region to region.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The present study observed a prevalence rate of 5.3% of conjunctivitis among hospitalized neonates. This is higher than 1.1% and 4.1% reported by Ochigbo et al from Nigeria and Goel et al from India respectively [3,18] , but lower than the 7.2%, 8.0% and 8.2% observed by other researchers from India, Togo and the United Kingdom respectively. [10,14,19] However, it has been pointed out that the incidence of neonatal conjunctivitis tends to vary widely from region to region.…”
Section: Discussioncontrasting
confidence: 55%
“…However, incidence rates of 1.1%among hospitalized neonates and 4.7/1000 live births have been reported. [3,4] Depending on the severity, the infection is potentially hazardous as it can lead to varying degrees of ocular and systemic…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 10 babies (0.6%) developed acute bilirubin encephalopathy. In 1 study done in Calabar, South Nigeria, the prevalence of ABE was estimated at 0.7%, 28 and another study in China showed a prevalence of 0.5% ABE in preterm neonates. 29 Among the preterm babies who developed ABE, for the majority, the bilirubin level was above 20.1 mg/dL.…”
Section: Discussionmentioning
confidence: 97%
“…Pakistan and Nigeria documenting rates of 27.6% and 19.6%, respectively [6]. Contributing to these elevated bilirubin levels are factors such as infection, ABO incompatibility, and glucose-6-phosphate dehydrogenase (G6PD) de ciency [7].…”
Section: Studies Across Various Regions Have Reported Varying Inciden...mentioning
confidence: 99%